2014
DOI: 10.1080/00224545.2014.972310
|View full text |Cite
|
Sign up to set email alerts
|

Nature Gives Us Strength: Exposure to Nature Counteracts Ego-Depletion

Abstract: Previous research rarely investigated the role of physical environment in counteracting ego-depletion. In the present research, we hypothesized that exposure to natural environment counteracts ego-depletion. Three experiments were conducted to test this hypothesis. In Experiment 1, initially depleted participants who viewed pictures of nature scenes showed greater persistence on a subsequent anagram task than those who were given a rest period. Experiment 2 expanded upon this finding by showing that natural en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Mayer et al, 2009;Hartig et al, 2003;see Buzzell & Chalquist, 2009). Recent research also finds that exposure to nature counteracts the negative effect of ego-depletion on selfcontrol performance (Chow & Lau, 2015). The present findings that ostracized people desire to connect to nature may imply that exposure to nature may ameliorate the pain and negative consequences of ostracism.…”
Section: Limitations and Future Directionsmentioning
confidence: 83%
“…Mayer et al, 2009;Hartig et al, 2003;see Buzzell & Chalquist, 2009). Recent research also finds that exposure to nature counteracts the negative effect of ego-depletion on selfcontrol performance (Chow & Lau, 2015). The present findings that ostracized people desire to connect to nature may imply that exposure to nature may ameliorate the pain and negative consequences of ostracism.…”
Section: Limitations and Future Directionsmentioning
confidence: 83%
“…According to Kaplan (1995) , these two types of fascination coexist. Soft fascination, characterized by moderate intensity, is experienced in aesthetically pleasant environments, whereas hard fascination is much more intense and appears in more attentionally demanding environments ( Heintzman, 2002 ), such as an exciting NBA match ( Chow and Lau, 2015 ). In our study, natural sounds could have supported restoration by inducing soft fascination in contrast to urban sounds evoking hard fascination.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the work and the workplace, Lee et al (2015) found that a forty second view of green roof can restore attention, similarly Chow and Lau (2015) found that people exposed to photos of nature restored their 'inner-strength' after depletion to have greater persistence in logic and reasoning tasks. Lottrup, Grahn and Stigsdotter (2012) found a significant relationship between decreased stress and workplace attitude, and visual and physical access to workplace greenery.…”
Section: Restorationmentioning
confidence: 99%